2012
DOI: 10.1103/physrevlett.109.265501
|View full text |Cite
|
Sign up to set email alerts
|

Revealed Architectures of Adsorbed Polymer Chains at Solid-Polymer Melt Interfaces

Abstract: We report the chain conformations of polymer molecules accommodated at the solid-polymer melt interfaces in equilibrium. Polystyrene "Guiselin" brushes (adsorbed layers) with different molecular weights were prepared on Si substrates and characterized by using x-ray and neutron reflectivity. The results are intriguing to show that the adsorbed layers are composed of the two different nanoarchitectures: flattened chains that constitute the inner higher density region of the adsorbed layers and loosely adsorbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

40
388
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(431 citation statements)
references
References 33 publications
40
388
3
Order By: Relevance
“…The revealed molecular weight dependence of the interfacial layer thickness is in stark contrast to what has been anticipated from theories [8][9][10][11][12] and to what can be expected from supported thin polymer film studies [20]. We see two possible reasons for this unexpected behavior: (1) PNCs require long annealing time to reach equilibrium [43,44]; or (2) the polymer chains experience a strong frustration in chain packing in the interfacial region due to the formation of large loops at higher MW.…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…The revealed molecular weight dependence of the interfacial layer thickness is in stark contrast to what has been anticipated from theories [8][9][10][11][12] and to what can be expected from supported thin polymer film studies [20]. We see two possible reasons for this unexpected behavior: (1) PNCs require long annealing time to reach equilibrium [43,44]; or (2) the polymer chains experience a strong frustration in chain packing in the interfacial region due to the formation of large loops at higher MW.…”
contrasting
confidence: 53%
“…Recently, Koga et al [20,29] explained the observed interfacial slowing down in supported thin films in terms of a bound loop layer (BLL) made of the loops of the adsorbed chains. According to them [20,29], the average height of the BLL provides a good estimate for the thickness of the DIL that experiences slower dynamics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been observed in ultrathin polymer films [16,17,20]. Mukherjee et al reported NTE below the T g in polystyrene (PS) films with thicknesses of several dozen nanometers, together with zero thermal expansion (ZTE) behavior [17].…”
Section: Observation Of Reproducibility Of Nte During Heating and Coomentioning
confidence: 97%
“…The importance of these findings in the pharmaceutical field cannot be overstated. Specular X-ray reflectivity (XRR) is a unique and powerful analytical method (Figure 2) that is frequently applied to condensed soft-matter films, including glass transition studies of ultrathin polymer films [16][17][18][19][20], but which has not been applied in amorphous sugar studies. XRR can evaluate the layered structure of a material, such as the film thickness, electron density, surface roughness, and interfacial width [21,22].…”
Section: Introductionmentioning
confidence: 99%